Comparative Analysis of the Gut Microbiota of Adult Mosquitoes From Eight Locations in Hainan, China - Kang, Xun (Front Cell Infect Microbiol, 2020)
The midgut microbial community composition, structure, and function of field-collected mosquitoes may provide a way to exploit microbial function for mosquito-borne disease control. However, it is unclear how adult mosquitoes acquire their microbiome, how the microbiome affects life history traits and how the microbiome influences community structure. We analyzed the composition of 501 midgut bacterial communities from field-collected adult female mosquitoes, including Aedes albopictus, Aedes galloisi, Culex pallidothorax, Culex pipiens, Culex gelidus, and Armigeres subalbatus, across eight habitats using the HiSeq 4000 system and the V3−V4 hyper-variable region of 16S rRNA gene. After quality filtering and rarefaction, a total of 1421 operational taxonomic units, belonging to 29 phyla, 44 families, and 43 genera were identified. Proteobacteria (75.67%) were the most common phylum, followed by Firmicutes (10.38%), Bacteroidetes (6.87%), Thermi (4.60%), and Actinobacteria (1.58%). The genera Rickettsiaceae (33.00%), Enterobacteriaceae (20.27%), Enterococcaceae (7.49%), Aeromonadaceae (7.00%), Thermaceae (4.52%), and Moraxellaceae (4.31%) were dominant in the samples analyzed and accounted for 76.59% of the total genera. We characterized the midgut bacterial communities of six mosquito species in Hainan province, China. The gut bacterial communities were different in composition and abundance, among locations, for all mosquito species. There were significant differences in the gut microbial composition between some species and substantial variation in the gut microbiota between individuals of the same mosquito species. There was a marked variation in different mosquito gut microbiota within the same location. These results might be useful in the identification of microbial communities that could be exploited for disease control.